2016
DOI: 10.18632/oncotarget.7986
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes in onco-hematological patients admitted to the intensive care unit with classic factors of poor prognosis

Abstract: Although the overall mortality of patients admitted to intensive care units (ICU) with hematological malignancy has decreased over the years, some groups of patients still have low survival rates. We performed a monocentric retrospective study including all patients with hematological malignancy in a ten-year period, to identify factors related to the outcome for the whole cohort and for patients with allogeneic hematopoietic stem cell transplantation (HSCT), neutropenia, or those requiring invasive mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…The early and short-term mortality rates for ICU admitted patients were high (cumulative mortality rates at 1 month 34% and at 6 months 53%). This is similar to previous data, which report a range of in-hospital mortality of 46-90% 1,[4][5][6][11][12][13][14][15][16][17][18][19][20][21][22] , with multi-organ dysfunction (illustrated by use of mechanical ventilation, vasopressor use, renal replacement therapy, significant liver enzyme elevation, high Acute Physiologic Assessment and Chronic Health Evaluation (APACHE) II, Sequential Organ Failure Assessment (SOFA), or Simplified Acute Physiology Score (SAPS) scores) being the most common predictor of death 1,[4][5][6][11][12][13][14][15][16][17][18][19][20][21][22] . This was further confirmed in larger studies including a literature review of observational studies encompassing 10,000 patients 23 , and a retrospective analysis of 7689 patients with hematologic malignancy admitted to the ICU 24 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The early and short-term mortality rates for ICU admitted patients were high (cumulative mortality rates at 1 month 34% and at 6 months 53%). This is similar to previous data, which report a range of in-hospital mortality of 46-90% 1,[4][5][6][11][12][13][14][15][16][17][18][19][20][21][22] , with multi-organ dysfunction (illustrated by use of mechanical ventilation, vasopressor use, renal replacement therapy, significant liver enzyme elevation, high Acute Physiologic Assessment and Chronic Health Evaluation (APACHE) II, Sequential Organ Failure Assessment (SOFA), or Simplified Acute Physiology Score (SAPS) scores) being the most common predictor of death 1,[4][5][6][11][12][13][14][15][16][17][18][19][20][21][22] . This was further confirmed in larger studies including a literature review of observational studies encompassing 10,000 patients 23 , and a retrospective analysis of 7689 patients with hematologic malignancy admitted to the ICU 24 .…”
Section: Discussionsupporting
confidence: 92%
“…ICU morbidity and mortality remain an important issue for patients with hematologic malignancy. Although predictors of mortality in patients admitted to ICU with hematologic malignancy are well described 1,[4][5][6][11][12][13][14][15][16][17][18][19][20][21][22] , there is a paucity of evidence that identifies the predictors of ICU admission in this population, or predictors of survival in hospitalized patients with hematologic malignancies. Overall, during a period of 5.5 years, 19% of patients with hematologic malignancies admitted to our tertiary care hospital were admitted to an ICU at least once, with 47% of these admissions to a high acuity (versus step-down) ICU.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, odds of mortality were higher for patients requiring RRT and in those with higher APACHE II scores indicating greater severity of illness, and these risk factors were constant in the mechanically ventilated subgroup. This finding echoes previous studies performed in oncologic populations …”
Section: Discussionsupporting
confidence: 92%
“…In several recent studies, neutropenia had been recognised as having no significant mortality effect among cancer patients admitted to ICU, and this has led to society guidelines recommending against the use of neutropenia as a triage criterion . However, a meta‐analysis of available studies on neutropenic critically ill cancer patients, published in 2018 by Georges et al ., found that neutropenia was independently associated with poor outcome, and thus should be considered during prognostication.…”
Section: Introductionmentioning
confidence: 99%
“…None of our patients presented with iatrogenic HLH following the administration of CAR T-cells or other immunotherapy [43]. Aggressive lymphoma further worsened the poor outcome due to the exacerbation of organ failure [44,45]. Patients admitted to the ICU with intracellular infections (mycobacteria, pneumocystosis, Herpesviridae) tended to have a greater mortality rate due to underlying severe comorbidities and/or immunosuppression.…”
Section: Discussionmentioning
confidence: 93%